Nanoceria neuroprotective effects in the light-damaged retina: A focus on retinal function and microglia activation. (November 2019) - Tisi, A.; Passacantando, M.; Ciancaglini, M.; Maccarone, R.
Abstract: The use of nanomaterials is an emerging therapeutic approach for the treatment of several pathologies. Cerium oxide nanoparticles have been studied for biomedical application, including neurodegenerative disorders, such as age-related macular degeneration in several animal models. The light damage model is characterised by oxidative stress upregulation followed by photoreceptor death and microglia activation in the outer retina. For this reason, the light damage model mimics some aspects involved in human age-related macular degeneration pathogenesis. In this review, we focus on the neuroprotective effects on retinal function and microglia activation in the light damage model, considering the administration of the nanoparticles both before and after the injury. The electrical responses of the retina and the microglia number and morphology are clearly modulated by the treatment, supporting the beneficial effects of cerium oxide nanoparticles to counteract the degeneration processes in the retina. Highlights: Nanoceria prevent and slow down retinal degeneration in several animal models. Nanoceria preserve and ameliorate retinal function. Nanoceria prevent and reduce inflammation.